Pentingnya Keterampilan Berbahasa Indonesia bagi Tenaga Kerja Pariwisata - Radjasa, Evan Ghani Hendra; Pramesti P, Bernadeta Sachi; Firdaus, Hudama Abdillah; Salsabila, Nadya Wefa; Ananta, Prysilya; Arum, Dewi Puspa (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the impact of language skills on tourism services. The type of research used is qualitative descriptive. Data collection techniques through observation, interviews, and documentation. Data analysis was carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The results of data analysis show that with this multi-method approach, this study is able to provide a comprehensive overview of the condition of tourism and the factors that affect it both in terms of theory and field practice.